Serum Metabolomics Associating With Circulating MicroRNA Profiles Reveal the Role of miR-383-5p in Rat Hippocampus Under Simulated Microgravity - Zhang, Hongyu; Chen, Jian; Wang, Hailong; Lu, Xin; Li, Kai; Yang, Chao; Wu, Feng; Xu, Zihan; Nie, Huan; Ding, Bai; Guo, Zhifeng; Li, Yu; et al. (Frontiers in Physiology, 2020)
Microgravity impacts various aspects of human health. Yet the mechanisms of spaceflight-induced health problems are not elucidated. Here we mapped the fusion systemic analysis of the serum metabolome and the circulating microRNAome in a hindlimb unloading rat model to simulate microgravity. The response of serum metabolites and microRNAs to simulated microgravity (SMG) was striking. Integrated pathway analysis of altered serum metabolites and target genes of the significantly altered circulating miRNAs with Integrated Molecular Pathway-Level Analysis (IMPaLA) software was mainly suggestive of modulation of neurofunctional signaling pathways. Particularly, we revealed significantly increased miR-383-5p and decreased aquaporin 4 (AQP4) - in the hippocampus. Utilizing Rrabies Virus Glycoprotein (RVG)-modified exosomes, delivery of miR-383-5p inhibited the expression of AQP4 not only in rat C6 glioma cells in vitro but also in the hippocampus in vivo. Using bioinformatics to map the crosstalk between the circulating metabolome and miRNAome could offer opportunities to understand complex biological systems under microgravity. Our present results suggested that the change of miR-383-5p level and its regulation of target gene AQP4 was one of the potential molecular mechanisms of microgravity induced cognitive impairment in the hippocampus.